Prevention of Transfusion-Transmitted Infections: Dilemmas - Zaaijer, Hans L. (Frontiers in Medicine, 2017)
To make blood components and blood products safe, many safety measures are applied to avoid transfusion-transmitted infections. Defining a balanced safety policy is not easy, we face several dilemmas: How safe should blood be? Should we opt for maximal or optimal safety? Are perceived threats real and relevant? Should blood be clean while food, air, or mosquitos are not? Is vCJD still a threat? It seems wise to discuss these issues more in the open.